2005
DOI: 10.1007/s00204-005-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A secretion by ATP-dependent membrane transporters in Caco-2 cells

Abstract: The ATP-dependent membrane transporters, P-gp, MRP2 and BCRP, localized in the luminal membranes of the intestines, liver and kidney, counteract absorption and increase excretion of xenobiotics and drugs. Previously, it has been suggested that the mycotoxin ochratoxin A (OTA) is a substrate for ATP-dependent transporters, and hence the absorption and secretion of OTA in the Caco-2 cell model was investigated. To this end, Caco-2 cells were cultured as confluent monolayers in bicameral inserts and the transepit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…From the results of this experiment, it was not possible to have an indication of whether the hydrolysis activity occurred in the medium due to an enzyme excreted out of the cell or if externally applied OTA was absorbed into the cell where the degradation process would have taken place. Previous studies have indicated that OTA is a substrate for different kinds of transporters facilitating not only the efflux of compounds but also cellular uptake (49). Actually, contradictory findings have been reported about the excretion of OTA-degrading enzymes by different fungal species.…”
Section: Discussionmentioning
confidence: 99%
“…From the results of this experiment, it was not possible to have an indication of whether the hydrolysis activity occurred in the medium due to an enzyme excreted out of the cell or if externally applied OTA was absorbed into the cell where the degradation process would have taken place. Previous studies have indicated that OTA is a substrate for different kinds of transporters facilitating not only the efflux of compounds but also cellular uptake (49). Actually, contradictory findings have been reported about the excretion of OTA-degrading enzymes by different fungal species.…”
Section: Discussionmentioning
confidence: 99%
“…Dietrich et al (2005) suggested the presence of organic anion transporters with the capacity to transport OTA in the jejunum, but Berger et al (2003) showed that these transporters were not implicated in OTA transport across Caco-2-cells. Another factor that may influence the OTA bioavailability is the finding that OTA is a substrate for the ATPBinding Cassette efflux-proteins MRP2 and BCRP in Caco-2-cells (Schrickx et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Substrates for these transporters are likely to appear in high concentrations in milk. Recently, it was shown that, for example, ochratoxin A is a substrate for BCRP (Schrickx et al 2006), which correlates with the high prevalence of ochratoxin A in human breast milk samples. In addition, it has been shown that aflatoxin B1 is a substrate for BCRP, making it likely that aflatoxin M 1 and aflatoxicol are also excreted actively into milk (Van Herwaarden et al 2006).…”
Section: Feed-to-milk Transmission Of Other Mycotoxins and Factors Afmentioning
confidence: 99%